INSTAGRAM AS SOCIAL MEDIA FOR TEACHING WRITING - MR, Elvira Rosyida; Seftika, Seftika (STKIP Muhammadiyah Pringsewu, 2019)
This study aims to describe students' perceptions of social media - Instagram in learning English, especially writing. This research is a type of qualitative research conducted on even semester students of the English study program at STKIP Muhammadiyah Pringsewu, Lampung. The data collection technique in this study uses questionnaires and structured interviews. Data analysis uses Interactive Model which consists of data collection, data reduction, data display, and conclusion drawing. The result shows that have a positive perception of the use of Instagram as a learning medium. Instagram creates fun classroom situations and helps students to be creative, communicative, and also collaborative with peers.